2019
DOI: 10.1073/pnas.1903422116
|View full text |Cite
|
Sign up to set email alerts
|

How lovebirds maneuver through lateral gusts with minimal visual information

Abstract: Flying birds maneuver effectively through lateral gusts, even when gust speeds are as high as flight speeds. What information birds use to sense gusts and how they compensate is largely unknown. We found that lovebirds can maneuver through 45° lateral gusts similarly well in forest-, lake-, and cave-like visual environments. Despite being diurnal and raised in captivity, the birds fly to their goal perch with only a dim point light source as a beacon, showing that they do not need optic flow or a visual horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Monkeys, for example, performed pitch and yaw head rotations while scanning the environment, but kept a steady gaze when they focused on a target [28]. In landing experiments, it has been shown that, similar to our bats, lovebirds kept a steady gaze in all axes ( pitch, yaw and roll) relative to a target, but more often in the second half of the flight, where there was a need for high precision during landing [14]. Zebra finches used head saccades in order to adjust their horizontal gaze while avoiding an obstacle and going through a window [13].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Monkeys, for example, performed pitch and yaw head rotations while scanning the environment, but kept a steady gaze when they focused on a target [28]. In landing experiments, it has been shown that, similar to our bats, lovebirds kept a steady gaze in all axes ( pitch, yaw and roll) relative to a target, but more often in the second half of the flight, where there was a need for high precision during landing [14]. Zebra finches used head saccades in order to adjust their horizontal gaze while avoiding an obstacle and going through a window [13].…”
Section: Discussionmentioning
confidence: 64%
“…Several previous studies found that animals stabilize their gaze during different tasks such as walking [2,6,9,15], running [28], flying [9][10][11]13], landing [14] and hovering [8,12], but more relevant to our study, relative to a target, where it has been shown that the fixation occurred after identifying a target. Monkeys, for example, performed pitch and yaw head rotations while scanning the environment, but kept a steady gaze when they focused on a target [28].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Quinn et al. (2019) show that birds responded effectively to unsteady flows given even limited sensory information. Katzmayr (1922) shows that fixed-wing aircraft can extract the energy in random gusts by clever transient rotations of the net aerodynamic force vector.…”
Section: Introductionmentioning
confidence: 99%
“… Perching at speed is amongst the most challenging flight behaviours that birds perform 1,2 , and beyond the capability of current autonomous vehicles. Smaller birds may touchdown by hovering 3-8 , but larger birds typically swoop upward to perch 1,2 – presumably because the adverse scaling of their power margin prohibits slow flapping flight 9 , and because swooping transfers excess kinetic to potential energy 1,2,10 . Perching is risky in larger birds 6,11 , demanding precise control of velocity and pose 12-15 , but it is unknown how they optimize this challenging manoeuvre.…”
mentioning
confidence: 99%